Analysis of Financial System Modeling for Integrated Petty Cash Based on Business Process Management - Bagas Brian Pratama; Kurnia Ekasari; Andi Kusuma Indrawan (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aimed to analyze the modeling of financial information systems for integrated petty cash using the concept of a Business Process Management System. The object of study was a training service company. This case study analysis was conducted to find problems in the study's object and then formulate. This study applied a qualitative method using Yin's (2009) explanatory case study analysis techniques with several stages ranging from data collection, case identification, and in-depth analysis to theory development and implications for settlement. The result of the study was a business process model based on Business Process Management Notation (BPMN) which could increase effectiveness and efficiency so that it had implications for improving the quality of the company's business processes.